Persepsi Kelas Menengah Muslim terhadap Dual Banking System dalam Membentuk Kekuatan Merek Perbankan Syariah - Lindiawatie Lindiawatie; Muzdalifah Muzdalifah (Universitas Indraprasta PGRI, 2017)
ABSTRACTThe goal of the research is knowing influence the perception of the dual banking system among the Middle Class of Moslems informing the brand strength of Islamic Banking. The method is by taking data through the questionnaire in the East/South Jakarta and Depok from February to July 2016. Data analysis using simple linear regression by the amounting was 320 respondents. The results that there are influences the perception among the Middle Class of Moslems against the dual banking system in building brand strength of the Islamic Bank (IB), that is 19% (R2). The brand strength of